Vascular Complications in Human Disease Mechanisms and Consequences - Abraham, David; Handler, Clive; Dashwood, Michael; Coghlan, Gerry (Springer London : Imprint: Springer, 2008)
Vascular disease provides a clear example of the inherent and practical relationship between basic science and clinical medicine. Basic science underpins the rationale of treatment and potential future therapeutic approaches; problems in clinical management often direct new lines of laboratory research. Progress in treatment cannot continue without this close collaboration and this book has been designed to review this fascinating collaborative field of medical science. As part of this evolving collaboration, Vascular Complications of Human Disease: Mechanisms and Consequences reviews the study, pathogenesis, management and treatment of some of the most common vascular diseases. The book includes discussions of approaches to gene therapy and aspects of regenerative medicine plus also physiology and pathogenesis, surgical and pharmacologic treatment, and complications. Clinical specialists caring for patients with any form of vascular disease must clearly understand the basic scientific rationale for disease pathogenesis. This book presents a cohesive review of our current understanding of the most important areas of clinical science and medicine in vascular disease and identifies areas for research in the future. It will be a useful reference for basic and clinical scientists, and clinical specialists in vascular surgery, cardiology, angiology, neurology and any discipline in which the vascular system plays a fundamental part in the disease process.